New employee recruitment selection decision support system using the web-based VIKOR method (Case Study: Gatarego II) - Efrem Manuel de Castro; Jaime da costa Lobo Soares (LPPMPK- Universitas Muhammadiyah Cileungsi, 2027)
Human resource needs are crucial for supporting a company's sustainability and progress. Appropriate workforce planning and recruitment are essential for objective selection and the production of qualified employees. However, manual employee selection processes can potentially lead to subjectivity and suboptimal decision-making. This study aims to design and build a decision support system that can assist the Human Resources (HR) department in selecting prospective employees more effectively and structuredly, and provide suitability recommendations based on predetermined criteria. The method used in this study is the VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) system, which uses four main criteria: written tests, interviews, skills, and experience. The system was developed web-based to facilitate data access and management, and allows for adjustment of criteria and assessment weights as needed. The system's testing results on four respondents from each division showed a score of 0.47, which is considered good. This indicates that the system is capable of facilitating the evaluation process and providing alternative decisions in the selection of prospective employees. Based on these results, it can be concluded that the developed VIKOR-based decision support system is capable of increasing the effectiveness and objectivity of the employee selection process and providing effective support for decision-making.